PENGARUH RASIO LIQUIDITAS, RASIO LEVERAGE DAN RASIO AKTIVITAS TERHADAP PERTUMBUHAN LABA, STUDY EMPIRIS PADA PERUSAHAAN MANUFAKTUR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sitanggang, Abdonsius (UNIKA Santo Thomas, 2013)
This study aims to identify and analyze the effect of liquidity ratio (curent ratio, leverage ratio (debt ratio) and the ratio of activity (total asset turnover) of the profit growth in consumer goods manufacturing companies listed in Indonesia Stock Exchange in 2008. The formulation of the problem is: Do curent ratio, debt ratio and total asset turnover effect on profit growth in consumer goods manufacturing companies listed in Indonesia Stock Exchange? The population of this research is the consumer goods manufacturing companies listed in Indonesia Stock Exchange in 2008. The technique of sampling is a sampling technique that is easy (purposive sampling). Samples taken in this study is the income statement and balance sheet total of 32 companies manufacturing consumer goods companies listed in Indonesia Stock Exchange in 2008. Data analysis and hypothesis testing is done by using a multiple linear regression model. The results were obtained curent Ratio (CR), Debt Ratio (DR), and Total Assets Turnover (TATO) and significant positive effect on earnings growth in consumer goods manufacturing companies listed in Indonesia Stock Exchange. Partially that curent Ratio (CR) bepengaruh negative and significant profit growth; Debt Ratio (DR) and a significant negative effect on earnings growth, and Total Assets Turnover (TATO) and significant positive effect on earnings growth in consumer goods manufacturing companies listed in Indonesia Stock Exchange.